Associação da cárie dentária com indicadores antropométricos do estado nutricional em pré-escolares - Foschini, Ana Lígia Rozato [UNESP] (2012)
The purpose of this study was to examine the association of dental caries with anthropometric indicators of nutritional status in preschool children in the city of Araraquara, SP. The sample was selected in a probabilistic stratifi ed way. A dental examination was conducted to investigate oral status indicators – dmft index. The weight and height of the children were measured. The anthropometric indicators of weight/height (WHZ), height/age (HAZ), weight/age (WAZ) and body mass index (BMIZ) were calculated. For the study of the probability of occur dental caries according to the nutritional status applying the logistic regression analysis. In order to compare the dmft index of preschool children according to the nutritional status was conducted by the Kruskal-Wallis test. 602 preschool children participated of the study. The mean dmft of the preschoolers was 1.22±2.23. Of the preschoolers 8.64% were wasted, 1.66% underweight and 1.00% stunted. High prevalence of excess weight was observed (38.37%), with prevalence of obesity of 15.78%. There was no signifi cant statistical difference (p=0.7128) for the dmft index according to the nutritional status of the children and the probability of the preschoolers to have dental caries is independent of the nutritional status.